The Years Before Gregory: Sources of Gregorian Chant I - Levey, Marie Therese (Bondi St Joseph Publications, 2006)
Marie Therese Levey is one of those rare creatures in chant studies who seek to communicate their knowledge of the subject to a broad as possible audience at the same time as maintaining sound principles of scholarship. The detail into which she delves was well proven by her doctoral thesis on liturgical manuscript migration (later published as The Migration of the Liturgy of the Divine Office of the Roman Rite into Portugal [North Sydney: St Josephs Publications, 1991]) which is an extraordinary volume tracing the particular history of a manuscript (Codex 4* of Arouca) and the wide influence that this single manuscript had on an entire national tradition. Her latest volume, though slim, provides an excellent starting point for those coming to the chant without specific knowledge of the environment in which it evolved, that is in the broadest terms Christian culture and in more specific terms the Catholic culture owing allegiance to the See of Peter. The volume under review is marked by Levey's tireless devotion to the subject and her considerable experience in introducing people to Gregorian Chant and teaching people who want to know more.
Keywords: Middle Ages (500-1400); Plainchant